Quantifying the relationship between GDP per capita and inequality in the Balkan region - Edgar J. Saucedo-Acosta (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: The paper aims to estimate the effect of inequality on the economic growth of Balkan countries for the period 2001-2017. In addition, the effect of capital stock on GDP per capita (GDPpc) for the Balkan countries was estimated. The low level of financial inclusion on the Balkan region produces an underinvestment of human capital and affects the low-income households, leading to an increase in inequality. Low levels of equality and capital stock negatively impact economic growth. Design/methodology/approach: An unbalanced panel data for Balkan countries for the period 2001-2017 was applied. The Balkans' neighboring countries were included, because a lot of Balkan countries lack data in many years, therefore more countries were added for statistical considerations. A random effects model was run. Finding: The Gini index negatively impacts the GDPpc of Balkan countries for the period 2001-2007. The reduction of inequality may increase the economic growth of the region. Capital stock positively impacts the GDPpc of the region. Research limitations/implications: Due to statistical considerations, we have included neighboring countries of the Balkans, because many Balkan countries do not have data for the entire series from 2001 to 2017. We have not estimated the bi-directionality of the relationship between inequality and GDPpc. The results suggest that public policies against inequality may increase economic growth. Therefore, governments of the region should apply public policies to reduce the income gap. Originality/value: There are many papers that have estimated the effect of the Gini index on economic growth in different regions around the world, but there are not many studies applied to the Balkan region. Therefore, this paper's novelty is the measure of the effect of the Gini index on the GDPpc of the Balkan region.
Keywords: O15; O52; 330; Technology Spillover; Foreign Direct Investment; Turkey